Television Culture. - Fiske, John (Taylor and Francis, 2010)
This revised edition of a now classic text includes a new introduction by Henry Jenkins, explaining 'Why Fiske Still Matters' for today's students, followed by a discussion between former Fiske students Ron Becker, Aniko Bodroghkozy, Steve Classen, Elana Levine, Jason Mittell, Greg Smith and Pam Wilson on 'John Fiske and Television Culture'. Both underline the continuing relevance of this foundational text in the study of contemporary media and popular culture. Television is unique in its ability to produce so much pleasure and so many meanings for such a wide variety of people. In this book, J.